The Inherent Human Aging Process and the Facilitating Role of Exercise - Lazarus, Norman R.; Harridge, Stephen D. R. (Frontiers in Physiology, 2018)
Arguably the best available depictions of the global physiological changes produced by age are the profiles of world record performance times in swimming, athletics and cycling, depicting the trajectory of decline in maximal integrated physiological performance capability. The curves suggest that the ageing process produces a synchronised, controlled decrease in physiological performance over the human lifespan irrespective of distance. Thus, the generation of the shape of the performance profile by age is independent of discipline, distance or phenotype. The specific times of performance are not the driving force in the production of the shape of the declining performance profile. The curve is generated by the ageing process operating on a physiology optimized for any given age. We hypothesise that with adequate training and facilities, this same profile and trajectory, if not actual performances, would be generated by all individuals who engage in sufficient physical activity/exercise (PAE). Unlike performance, data obtained from examining individual physiological systems or tissues do not give information on the unceasing and changing global integrating functions of the ageing process. However, these data do give valuable information about the integrity of physiological systems at a particular age and allow a direct comparison to be made between the effects of inactivity and PAE. PAE has been shown to have global protective effects on physiological systems and thus facilitates the ageing process by maintaining physiological integrity. There is emerging evidence which suggests that physiological regulation of ageing may be multi-compartmentalised. We do not advocate PAE as a panacea, but all the evidence indicates that PAE is far superior to any other alternative for achieving optimal ageing.